Antimicrobial activity of important Indian medicinal plants against Pyogenic infection - P. Ponmurugan, B. Bagyalakshmi, D. Sridhar (Journal of Phytology, 2009)
The antimicrobial activity of crude extracts of five medicinal plants used in traditional Indian medicine was tested against fiveÃ‚Â Ã‚Â important Ã‚Â pyogenic bacteria.They are Streptococcus pyogenes, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa.Streptococcus pneumoniae. Of the five medicinal plants used only three were showed considerable antimicrobial activity against one or more species of microorganisms tested. Among the three solvents used the most effective extract was found to be methanol extraction. The most effective antimicrobial plant was identified as Glycyrriza glabra followed by Dathura metal, Coccinia grandis. Least activity was observed inÃ‚Â Sida spinosa, and Lab lab purpureus.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â